Keripik Daun Mangrove (KIPMANG): Inovasi Pangan Untuk Peningkatan Ekonomi Masyarakat Pesisir Kampung Bulo, Kecamatan Tabukan Selatan, Kabupaten Kepulauan Sangihe, Sulawesi Utara - Bilqis, Dewi Shofya; Lawendatu, Angryani Enjela; Janis, Ronaldo Ferdinan; Mandalika, Ervina Dian; Sambeka, Yana; Cahyono, Eko; Tanod, Wendy Alexander (Abdimas Indonesian Journal, 2023)
Bulo Village is in South Tabukan, Sangihe Islands, North Sulawesi. One of the potential natural resources of Bulo Village that has yet to be utilized is mangrove leaves. Mangrove leaves can be used in processed food products, such as chips. This community service aims to transfer science and technology to increase the economic value of mangrove plants by diversifying food products in the form of mangrove leaf-based chips. This community service activity was carried out in several stages: 1). Location survey and mangrove species identification; 2). Formation of business groups; 3). training and mentoring in the production of KIPMANG-Mangrove Leaf Chips; 4). Education on simple business analysis of KIPMANG products. The identification results showed that the dominant type of mangrove, Rhizophora sp., grows in the Bulo Village. Kapitalaung recommended that the 12 Bulo community join the mangrove leaf chips business group. The business group can produce and package KIPMANG with original and balado variants. The business group also understands the principles of business analysis of KIPMANG products. This community service activity can increase the knowledge and skills of the Bulo community. It can also improve the economy of the coastal communities of Bulo Village through village-owned business groups.